First record of Coffee Ringspot Virus (CORSV) in westrn Bahia - Almeida, Eduardo Melo; Figueira, Antonia Reis (Coffee Science - ISSN 1984-3909, 2014)
The coffee ringspot, whose etiologic agent is the Coffee ringspot virus (CoRSV), is a disease that has been causing damage in defoliation in coffee plantations in the states of Minas Gerais and São Paulo. The damage ranging from the defoliation accentuated, premature fall of fruits and loss of quality. This work was carried out a study to identify the stainoverride in coffee farms in Western Bahia, Brazil. In Luís Eduardo Magalhães and São Desiderio counties, located in Western Bahia - Brazil, were observed incidences up to 45,6% of coffee plants with ringspot symptoms. Mechanical inoculation of infected material in indicator plants for viruses, Chenopodium ambrosioides, Amaranthus deflexus and Chenopodium quinoa induced typical symptoms confirming the infection by Coffee ringspot virus (CoRSV). This is the first record of CoRSV in Western Bahia, indicating that this virus probably is present in all coffee plantations of the region, established in places with higher temperatures, since this is a factor considered ideal for viral multiplication.